2022
DOI: 10.1590/fst.23222
|View full text |Cite
|
Sign up to set email alerts
|

Thin-layer drying characteristics of Easter lily (LiliumlongiflorumThunb.) scales and mathematical modeling

Abstract: This study investigated the effects of temperature on the drying behavior and kinetic features of lily scales. A series of experiments were carried out at 65, 75, and 85 °C to dry the scales in a laboratory air-ventilated oven dryer. Drying temperature was found to significantly affect drying times and drying rates. The rate curves suggested that the drying process of lily scales occurred entirely within the descending rate period. During the simulation of drying kinetics, Page and Logarithmic models were prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This is due to the significant difference in steam pressure between the fruit slices and the surrounding environment at a higher temperature. As a result, the rate of water migration gradually decreased from the inside to the outside of the sample (Wang et al, 2022a). The study by Jiang et al (2021) found that the average migration rate of moisture inside wheat grains was smaller than the average evaporation rate outside wheat grains.…”
Section: Drying Rate Curvementioning
confidence: 97%
“…This is due to the significant difference in steam pressure between the fruit slices and the surrounding environment at a higher temperature. As a result, the rate of water migration gradually decreased from the inside to the outside of the sample (Wang et al, 2022a). The study by Jiang et al (2021) found that the average migration rate of moisture inside wheat grains was smaller than the average evaporation rate outside wheat grains.…”
Section: Drying Rate Curvementioning
confidence: 97%
“…This parameter accounts for various mechanisms, including vapor diffusion, capillarity, molecular diffusion, and liquid diffusion through the solid pores (Vallespir et al, 2019). As shown in Table 3, the effective moisture diffusivity for biological samples is typically measured within 10 −8 to 10 −12 m 2 /s (Wang et al, 2022), and in this study, the effective moisture diffusivity values of whole and sliced ginseng were within the range of 3.42 × 10 −12 –1.03 × 10 −11 and 1.03 × 10 −11 –2.05 × 10 −11 m 2 /s, respectively. The effective moisture diffusivity values of both whole and sliced samples were proportional to the drying temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The Arrhenius equation is the most acceptable expression to account for the effect of temperature on the rate of AA destruction in food systems. The Arrhenius relationship for the temperature dependence for the rate constant degradation K is as follows (Equation 2) (Wang et al, 2022):…”
Section: Arrhenius Equationmentioning
confidence: 99%